Human Nature, the Environment, and Behaviour: Explaining the scope and geographical scale of financial decision-making. - Clark, G (School of Geography and Environment (University of Oxford), 2009)
This paper explores two inter-related themes. One addresses fundamental questions of human nature, arguing that conventional theories of behaviour lack a credible appreciation of the interaction between cognition and context (or what is often termed as the 'environment'). The second considers decision-making under risk and uncertainty, focusing upon customary behaviour and the significance or otherwise of conscious deliberation. My argument is intended to be both critical and constructive, exploring the claims of the emerging school of behaviouralism associated with Kahneman and Tversky now sweeping the social sciences. Most importantly, it is argued that economic geography should take more seriously the nature and scope of behaviour recognising its attributes including related social and cultural aspirations. These ideas are illustrated by a set of recent studies dealing with financial decision-making and individuals' attitudes towards risk in personal and occupational pension plans. The importance of this project lies in the urgent need to understand the diversity of behaviour of men and women in, and through, the communities in which they live without being reduced to yet another version of environmental determinism. In conclusion, implications are drawn for understanding the global financial crisis.